Home medication review and drug-related problems in patients with chronic diseases at primary health centers in Yogyakarta, Indonesia: A cross-sectional multicenter study - Ningrum, Vitarani Dwi Ananda; Yunilistianingsih; Khotimah, Muslimatul; Shintia, Nirma Atin; Efendi, Septia Rahayu; Dewani, Cindy Pramudyah; Andini, Hana Trisna; Yuantari, Rahma (Belitung Nursing Journal, 2026)
Background: The high incidence of Drug-Related Problems (DRPs), including medication adherence among patients with chronic diseases, especially during no direct monitoring by health workers, becomes a challenge to therapy success. Home Medication Review (HMR) is an alternative solution in primary healthcare services to avoid further complications. Objective: This study aimed to analyze DRPs, their affecting factors, and DRP interventions for patients with chronic diseases in primary health centers (Puskesmas) through HMR. Methods: A quantitative, cross-sectional observational study using purposive sampling was conducted in several Puskesmas in Yogyakarta from February to May 2023. The collaborative HMR involved healthcare providers at each Puskesmas. DRPs were assessed based on observations and semi-structured interviews. The DRP classification followed PCNE V9.1, and medication adherence was measured using both pill counts and self-report via the MARS-10 questionnaire. Data were analyzed using SPSS 25.0 to perform logistic regression with a 95% confidence level. Results: A total of 544 patients, comprising 269 adults and 275 older patients, were involved. Older patients experienced more DRPs than the adults (94.2% vs 84.8%). The most DRP experienced by both age groups was ineffective therapies, with the two most frequent causes being related to patient factors. Among the adults, hypertension comorbidity, number of medications, and BMI factors were associated with DRPs (p < 0.05). In contrast, no factors correlated with DRPs in the older patients. There was fair agreement between pill count and MARS-10 regarding medication adherence for both adults and older patients (kappa coefficients of 0.298 and 0.355, respectively). Conclusion: Patients in primary health facilities with hypertension and using at least three medications have over a three-fold increased risk of experiencing DRPs. Healthcare providers, including pharmacists, nurses, and physicians, should collaborate to identify medication-related issues and provide personalized advice and management plans to enhance medication adherence. This study highlights the need for a standardized, structured HMR program, not merely as a patient home visit but also to better control chronic diseases.